Estudo comparativo do efeito da música e da educação em saúde no desempenho cognitivo, sintomas depressivos e estresse percebido de idosos residentes em área rural - Moura, Fernanda Gomez de (Universidade Federal de São Carlos, 2019)
Data from the Brazilian demographic census show that 15% of the population comments years or more are from rural life in rural areas. Studies on positive indicators of music with music and educational actions in the health of the elderly, however are few or so numerous, with the rural population. Objective: To analyze the effect of language with music and health education does not make cognitive difference, depressive symptoms and the effort of attention to the elderly in a rural area of a municipality in the interior of. Method: This is a feasibility study based on the assumptions of the non-pharmacological randomized clinical trial. Participating in the study were 26 people aged 60 years and over, divided into two groups: Music Intervention Group (G1 = 15) and Health Education Group (G2 = 11). As assessment instruments were used: Addenbrooke Cognitive Examination - Revised (ACE-R) with evaluation of Attention / Orientation, Memory, Verval Fluency, Ligand and visual-spatial skills; Geriatric Depression Scale (GDS-15), Perceived Stress Scale (PSS) before and after interventions. Facilities were provided at the Family Health Unit and were held weekly, lasting one hour each, totaling ten sessions for each group. Wilcoxon's test (Z) was used to compare pre and post-intervention moments. Results: Both groups are predominantly based on women. G1 was on average 2.84 years older than G2, but without statistical significance. The groups were isolated because they were divided into instrumental activities of daily living and used polypharmacy. With regard to the overall performance of the battery, the ACE-R, the motor groups results in the postintervention measure, with G1 being greater than the greater effect (Z = 2.84). G1 presented better scores in all domains of ACE-R, with the exception of Attention /Orientation. The G2 presented improvement in all domains, Memory. The greatest effect was not the G1 for the Memory domain (Z = 3.30, p =, 001) and for G2 the best set of effects in Viso-spatial Skills (Z = 2.67, p = .007) . In relation to the evaluation of mood, both groups were portrayed in GDS with similar genres (G1: Z = -2,14, G2: Z =-2,20), in G1 the scores were reduced in PSS (Z = -2.360, p = 0.18). Conclusion: the results were 2 groups were similar, however the group that received the information system showed better in memory shortage and increased considerably the stress scores. The results show an importance of integrative and complementary strategies for cognitive performance, perceived risk and depressive symptoms of elderly people living in rural areas.
Comparative study of the effect of music and education in health in cognitive performance, depressive symptoms and perceived stress of old residents in a rural area
Keywords: População rural; Idosos; Cognição; Educação em saúde; Intervenção com música; Rural population; Elderly; Cognition; Health education; Intervention with music; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL